Jungfraujoch: 38 GB/s Real-Time Serial Crystallography – Data Acquisition and Live Indexing Feedback - Duan, Jiaxin (Lund University, 2026)
Significant growth in data presents a critical challenge for macromolecular crystallography at the fourth-generation synchrotrons. We introduce an updated version of the Jungfraujoch server, reaching data throughput of 38 GB/s from a 9 Mpixel JUNGFRAU detector (JUNGFRAU 9M) operating at 2 kHz, and improving data analysis capabilities with spot finding and indexing. These capabilities provide real-time information that can inform experimental decisions, including which data to retain on disk. In a serial crystallography demonstration at MicroMAX, we illustrate how live indexing integrates into the data collection workflow and show that its results are consistent with offline analysis. By enabling operation of Jungfraujoch on modern x86 hardware, we are lowering the barrier to adopting the system at sources beyond Swiss Light Source 2.0 and MAX IV

Data collected with DCM: /data/visitors/micromax/20230350/20240521/raw/LysozymeJet8/LysozymeJet8-lysozyme1/LysozymeJet8-lysozyme1_1_master.h5 - Flux: 5x10e12 ph/s

Data collected with MLM: /data/visitors/micromax/20230350/20240521/raw/run2/LysozymeJet5/LysozymeJet5-lysozyme1/LysozymeJet5-lysozyme1_2_master.h5 - Flux: ~10e14 ph/s

Data collected with MLM: /data/visitors/micromax/20230350/20240521/raw/run2/LysozymeJet5/LysozymeJet5-lysozyme1/LysozymeJet5-lysozyme1_10_master.h5 - Flux: ~10e14 ph/s
Keywords: Physical Sciences; Fysik